Penerapan Metode Design Thinking Dalam Perancangan UI Aplikasi Audiolife Stimulasi Sensorik dan Motorik Anak - Magdalena Amelia Rizky; Wahyu Teja Kusuma; M Syauqi Haris (Jurnal Informatika dan Komputer, 2026)
Smartphones have now become one of the technologies used every day, can make savings and easy learning media. One of them is parents, by utilizing smartphones parents can monitor and stimulate their children's growth and development, especially in sensory and motoric. Using the application of design thinking methods that produce user interface designs to meet user needs. Through five stages, namely empathize, define, ideate, prototype, and test. Research on the design of the audiolife application user interface for children's sensory and motoric stimulation can answer the challenge of low knowledge and stimulation in children in Indonesia. Children who lack stimulation can experience abnormal growth and development or permanent problems. This application is designed for free, so it can be accessed by all groups. This solution opens up great opportunities for further application product development on a wider scale. This research has great potential to be developed into a superior product that is beneficial for the future of children, relevant for developers, education, and researchers who want to contribute through technology.